2012
DOI: 10.5539/elt.v6n1p92
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Textual Input Enhancement and Explicit Rule Presentation on Iranian Elementary EFL Learners’ Intake of Simple Past Tense

Abstract: The present study investigated the impact of textual input enhancement and explicit rule presentation on 93 Iranian EFL learners' intake of simple past tense. Three intact general English classes in Tabriz Azad University were randomly assigned to: 1) a control group; 2) a TIE group; and 3) a TIE plus explicit rule presentation group. All participants were given 3 reading texts and comprehension questions to complete. For participants in groups 2 and 3 the input was textually enhanced through bolding. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…When the learners paid attention on that form, they were more attracted and focus on the target forms. The finding of this study also showed that TE was an effective focus on form technique, at least for learning NP, which is in line with Nahavandi & Mukundan (2013) who supported the effectiveness of TE.…”
Section: Hypothesis Testingsupporting
confidence: 89%
“…When the learners paid attention on that form, they were more attracted and focus on the target forms. The finding of this study also showed that TE was an effective focus on form technique, at least for learning NP, which is in line with Nahavandi & Mukundan (2013) who supported the effectiveness of TE.…”
Section: Hypothesis Testingsupporting
confidence: 89%
“…Furthermore, Widdowson (1990) claims, when learners are left to their own resources they "do not very readily infer knowledge of the language system from their communicative activities" (p.167). TIE involves highlighting special features of input that may go unnoticed under normal circumstances through typographically manipulating them (Nahavandi & Mukundan, 2013d). Therefore, based on the main objective of the study which was enhancing learners' vocabulary knowledge, the present study aimed at understanding if TIE as an implicit method of teaching would bring about any changes in Iranian elementary EFL learners vocabulary knowledge or not.…”
Section: Textual Input Enhancement (Tie)mentioning
confidence: 99%
“…Furthermore, in order to check the students' intake of vocabulary both in pre and posttests multiple-choice recognition tests were used. The reason for using this kind of tests was based on (Leow, 1997;Overstreet, 1998;Nahavandi & Mukundan, 2013d) who ascertained the effectiveness of these kinds of tests in exploring the impact of TE on intake. First, two researcher made parallel versions of a multiple-choice recognition test namely as (A & B), one for pretest and one for posttest, with 30 questions each scoring 1 were developed.…”
Section: Demographic Questionnaire Reading Texts and Multiple-choice Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Textual enhancement, as to the acquisition of the English Past Simple Tense, was also investigated by Nahavandi and Mukundan (2013). The 2 authors combined textual input enhancement with rule presentation in 1 of their 3 groups and reported statistically significant beneficial effects in comparison to a control group.…”
Section: Thmentioning
confidence: 99%